Anti‐spike IgG antibody kinetics following the second and third doses of BNT162b2 vaccine in nursing home residents. Issue 9 (10th May 2022) - Jeulin, Helene; Labat, Carlos; Duarte, Kevin; Toupance, Simon; Nadin, Gregoire; Craus, Denis; Georgiopoulos, Ioannis; Gantois, Isabelle; Goehringer, François; Benetos, Athanase
Abstract: Background: Duration of post‐vaccination protection against COVID‐19 in nursing home (NH) residents is a critical issue. The objective of this study was to estimate the duration of the IgG(S) response to the mRNA BNT162b2 vaccine in NH residents with (COV‐Yes) or without (COV‐No) history of SARS‐CoV‐2 infection. Methods: A 574 COV‐Yes and COV‐No NH residents were included in 2 cohorts: Main ( n  = 115, median age 87 years) or Confirmatory ( n  = 459, median age 89 years). IgG(S) quantification was carried out at three different time points following the BNT162b2 vaccine: three (1st) and seven (2nd) months after the 2nd dose, and 1 month after the 3rd dose (3rd quantification) in the Main cohort, and twice (2nd and 3rd) in the Confirmatory cohort. The seroneutralization capacity according to COVID‐19 history was also measured in a subgroup of patients. Results: Neutralization capacity was strongly correlated with IgG(S) levels ( R 2 :76%) without any difference between COV‐Yes and COV‐No groups for the same levels of IgG(S). After the 2nd dose, duration of the assumed robust protection (IgG(S) >264 BAU/ml) was two‐fold higher in the COV‐Yes vs. COV‐No group: 12.60 (10.69–14.44) versus 5.76 (3.91–8.64) months, with this advantage mainly due to the higher IgG(S) titers after the 2nd dose and secondary to a slower decay over time. After the 3rd dose, duration of robust protection was estimated at 11.87 (9.88–14.87) (COV‐Yes) and 8.95 (6.85–11.04) (COV‐No) months. These results were similar in both cohorts. Conclusions and Relevance: In old subjects living in NH, history of SARS‐CoV‐2 infection provides a clear advantage in the magnitude and duration of high IgG(S) titers following the 2nd dose. Importantly, the 3rd dose induces a much more pronounced IgG(S) response than the 2nd dose in COV‐No subjects, the effect of which should be able to ensure a prolonged protection against severe forms of COVID‐19 in these subjects.